The Late Period Mutazilite Mufassir: A Biographical Study of Hākim Al-Jushamī - Didik Andriawan; Hakan Uğur; Ali Akpınar; Ali Dadan (Tribakti: Jurnal Pemikiran Keislaman, 2024)
This article aims to explore Hakim al-Jushamī, a Mutazilite mufassir from the late period, through a biographical analysis, as well as to delve into his exegetical ideas. He is recognized as a trailblazer in Islamic thought, particularly within the Mu’tazila school, and has made significant contributions to the field of tafsir (Quranic exegesis). His persona is regarded as the bridge reinstating the interrupted scholarly lineage between Zamakhsharī and the earlier commentators of tafsir. His principal contribution to the field of tafsir is al-Tahdhīb fi al-Tafsīr, a compilation that amalgamates the diverse viewpoints of Mu’tazila scholars whose narratives are not documented in other works. This article is centered on two primary objectives: (1) A biographical analysis of Jushamī within the context of Mu’tazila scholarship. (2) An examination of Jushamī in his capacity as a Mu’tazila mufassir and scholar. The research employs a qualitative methodology, adopting a biographical study approach through a literature review. The research employs data reduction, data presentation, and conclusion as its analytical techniques. The research analysis encompasses an examination of the individual in the socio-historical context and a critique of Mu’tazila philosophy and tafsir (Quranic exegesis) as manifested in his works. The findings revealed that: (1) Jushamī’s life, from a socio-historical perspective, exhibits a close association with Mu’tazila and positions him as an integral component of the Mu’tazila intellectual lineage that connects Zamakhsharī to earlier scholars. (2) His diverse body of work is primarily centered on advocating and defending the Mu’tazila doctrine. (3) Jushamī is regarded as a representation of the concluding era of Mu’tazila mufassirs before the group eventually vanished.